2020
DOI: 10.2147/nss.s258471
|View full text |Cite
|
Sign up to set email alerts
|

<p>Glasgow Sleep Effort Scale: Translation, Test, and Evaluation of Psychometric Properties of the Persian Version</p>

Abstract: The purpose of the current study is to translate, test and evaluate the psychometric properties of the Glasgow Sleep Effort Scale (GSES) in Persian language. Methods: Participants consisted of two samples: a clinical sample of 120 patients (58%) with insomnia disorder meeting DSM-5 criteria for insomnia and a non-clinical sample of 110 participants (42%) with normal sleep. Both samples completed the following measures: GSES, Pittsburg Sleep Quality Index, Insomnia Severity Index, Dysfunctional Beliefs and Atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…It has further been suggested that sleep effort is an underlying mechanism that explains discrepancies between subjective and objectively measured sleep 33 . Some studies have shown that sleep effort predicts subjective insomnia severity, 28,29 whereas dysfunctional beliefs predict objective insomnia outcomes 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has further been suggested that sleep effort is an underlying mechanism that explains discrepancies between subjective and objectively measured sleep 33 . Some studies have shown that sleep effort predicts subjective insomnia severity, 28,29 whereas dysfunctional beliefs predict objective insomnia outcomes 29 .…”
Section: Discussionmentioning
confidence: 99%
“…It has further been suggested that sleep effort is an underlying mechanism that explains discrepancies between subjective and objectively measured sleep. 33 Some studies have shown that sleep effort predicts subjective insomnia severity, 28,29 whereas dysfunctional beliefs predict objective insomnia outcomes. 29 Hertenstein et al 29 also showed in their study that polysomnography-determined total sleep time was associated with dysfunctional beliefs and attitudes about sleep.…”
Section: Discussionmentioning
confidence: 99%